2017
DOI: 10.19082/3896
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Coenzyme Q10 on echocardiographic parameters of patients with Duchenne muscular dystrophy

Abstract: BackgroundMyocardial damage is a common complication in patients with Duchenne muscular dystrophy (DMD) that occurs due to myocardial replacement by fat and fibrosis. In recent years, efforts have been made toward finding new pharmacological agents with fewer complications which can be used as prophylactic before the symptoms. Coenzyme Q10 plays a central role in production of bioenergy in heart muscle and antioxidant in reperfusion condition of myocardial damaged muscle and leads to membrane stability and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
(40 reference statements)
0
5
0
1
Order By: Relevance
“…CoQ 10 is also a potent antioxidant and may counteract the excessive ROS production in dystrophic myofibres. The compound was tested in different clinical trials in DMD patients with encouraging results: CoQ 10 supplementation ameliorated the impaired myocardial function and physical performance [179][180][181], although no significant improvement in echocardiographic parameters was revealed [182]. Interestingly, idebenone, a synthetic analogue of CoQ10 sharing its antioxidant profile, is at an advanced stage of development for treating cardiorespiratory dysfunction of DMD patients [182][183][184].…”
Section: Coenzyme Q 10mentioning
confidence: 99%
“…CoQ 10 is also a potent antioxidant and may counteract the excessive ROS production in dystrophic myofibres. The compound was tested in different clinical trials in DMD patients with encouraging results: CoQ 10 supplementation ameliorated the impaired myocardial function and physical performance [179][180][181], although no significant improvement in echocardiographic parameters was revealed [182]. Interestingly, idebenone, a synthetic analogue of CoQ10 sharing its antioxidant profile, is at an advanced stage of development for treating cardiorespiratory dysfunction of DMD patients [182][183][184].…”
Section: Coenzyme Q 10mentioning
confidence: 99%
“…Randomized trials ( n = 10) studied the effects of ACEI or ACEI plus BB ( n = 4), 8,9,16,20 aldosterone inhibitors ( n = 2), 29‐31 and four other novel therapies 26‐28,32 …”
Section: Resultsmentioning
confidence: 99%
“…Growth hormone administered over 3 months resulted in an increased LV mass, the significance of which is unclear 27 . After 6 months of treatment with coenzyme Q10, LV function did not change 32 . A sildenafil trial was stopped prematurely due to increases in LV end‐systolic volume at 6 months in patients receiving active therapy 28…”
Section: Resultsmentioning
confidence: 99%
“…A Phase 3 clinical study reported that CoQ10 could prevent the loss of respiratory function in DMD patients. The favorable safety and tolerability profiles of CoQ10 make it a potential option to ameliorate the ROS in DMD ( Salehi et al, 2017 ).…”
Section: Therapeutic Strategies Targeting the Secondary Downstream Pathological Mechanismsmentioning
confidence: 99%